1994
DOI: 10.1128/mcb.14.3.1796
|View full text |Cite
|
Sign up to set email alerts
|

Specific initiation at an origin of replication from Schizosaccharomyces pombe.

Abstract: Using a genetic assay for efficient autonomous replication, we have isolated from Schizosaccharomyces pombe a 6.2-kb fragment which shows the properties expected of an origin of DNA replication in S. pombe. A 2.8-kb subclone of the fragment has the same replication properties. Two-dimensional gel analysis of replication intermediates throughout plasmids carrying the 6.2-or 2.8-kb fragments shows that replication initiates only in a specific region, which can be localized to within several hundred base pairs, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
46
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 60 publications
8
46
0
Order By: Relevance
“…The prediction that proteins involved in initiation should bind to origins has been confirmed in prokaryotes (44,47,81,90,99) and mammalian DNA viruses (24,29,88), and recent data obtained for S. cerevisiae demonstrate that ARSs are footprinted by a multiprotein complex referred to as the origin recognition complex (4,6,42,89). Finally, electron microscopy (56,85,107) and two-dimensional gel electrophoresis studies of bacterial (83,84), yeast (10,19,57,74,127), and mammalian viral (45,91,101,105) ARSs reveal structures consistent with bidirectional replication initiating from these origins in vivo.…”
mentioning
confidence: 84%
“…The prediction that proteins involved in initiation should bind to origins has been confirmed in prokaryotes (44,47,81,90,99) and mammalian DNA viruses (24,29,88), and recent data obtained for S. cerevisiae demonstrate that ARSs are footprinted by a multiprotein complex referred to as the origin recognition complex (4,6,42,89). Finally, electron microscopy (56,85,107) and two-dimensional gel electrophoresis studies of bacterial (83,84), yeast (10,19,57,74,127), and mammalian viral (45,91,101,105) ARSs reveal structures consistent with bidirectional replication initiating from these origins in vivo.…”
mentioning
confidence: 84%
“…Genetic studies have shown that S. pombe origins contain multiple redundant elements, which can be deleted or replaced by other AT-rich sequences without significantly affecting activity (14)(15)(16)18). Most of the chromosomal origins that have been analyzed in S. pombe fire in only a minority of cell cycles, suggesting that the number of potential origins is greater than the number actually used in any given cell cycle (11,13,17,(19)(20)(21). These properties are not easily reconciled with the classical replicon model.…”
mentioning
confidence: 88%
“…Origins of DNA replication in Schizosaccharomyces pombe differ in a number of ways from those of S. cerevisiae (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…In this organism, as in S. cerevisiae, initiation takes place at discrete sites in the chromosome and each of these sites corresponds to an ARS element (13,22,73,77). S. pombe ARS elements are more than fourfold larger than those of S. cerevisiae, and they are characterized by an abundance of asymmetric AT-rich sequence motifs (14,21,80).…”
Section: Although the Nature Of Higher Eukaryotic Replication Originsmentioning
confidence: 99%